Ghrelin polymorphism/TRPV1 receptor expression in Egyptian IBS patients. (April 2022) - Samy, Walaa; El Gebaly, Ahmed; Ahmed, Nabila H.; Talaat, Aliaa
Abstract: Introduction/objective: Irritable bowel syndrome is a functional gastrointestinal disorder. Ghrelin is a peptide hormone which affects gastrointestinal motility. We have studied the association between ghrelin gene polymorphism, ghrelin expression, and their effect on TRPV1 correlating this with IBS manifestations in the Egyptian patients. Methods: Participants included 60 IBS patients meeting the Rome III criteria and 60 controls similar in age and gender were recruited. Whole blood samples were used for genotyping of Ghrelin polymorphisms rs696217. Colonic biopsies were processed for mRNA expression analysis of ghrelin and TRPV1. Results: The rs696217 GG genotype frequency was higher in patients (78.3%) compared to controls (57%). According to GTgenotype there was significant difference between IBS and control group: 21.7%, 43% respectively (p = 0.0126). In allele frequency distribution, G allele in the IBS group was 87.5% while in the control group was 74%.T allele presents in 12.5% of IBS patients and 26% in the control group (p = 0.010). The genotype frequencies did not significantly differ between IBS subtypes. TRPV1 mRNA levels in were significantly increased in IBS patients than in controls (p < 0.05), while GHRL mRNA expression was significantly decreased (p < 0.05). The IBS-C group showed significantly higher levels of TRPV1 and lower levels of GHRL mRNA expression (p < 0.05) Conclusions: we showed that ghrelin rs696217 might have a role in IBS, as those patients carrying the GG genotype showed a significant decrease in ghrelin mRNA expression, with a subsequent significant increase in TRPV1 gene expression, and could explain some of the IBS manifestations.